Restoring probation: A declaration of independence. (September 2019) - Priestley, Philip; Vanstone, Maurice
In light of the 2019 announcement by the then Secretary of State for Justice, David Gauke, that the probation service is to be re-nationalised, this paper reflects on what forms a more radical restoration might take. In essence, the paper makes a case for probation to be re-constituted as a moral enterprise; an independent agency based in the community, staffed by skilled and idealistic but pragmatic practitioners and managers, and informed by evidence of what is most likely to help people lead offence-free lives.